Web-based infrastructures : a 4D framework - Mukhopadhyay, Sanmay; Smith, Cooper; Muniz, Mayra; Harris Kern's Enterprise Computing Institute (Upper Saddle River, NJ : Prentice Hall, 2003)
This book present a framework for planning and managing the IT initiatives that are crucial to any Web-based business strategy. Finding the right formula, for adapting IT Infrastructures and business models real world business conditions in today's economy is more challenging than ever. The resulting "4-Dimensional Framework" consists of a 4X4 matrix of fundamental concepts, rules and practices. Part I focuses on the key drivers (Business, People, Technology, and Process). Part II covers the key phases of business analysis and project management. Part III explores the disciplines required to coordinate and implement specific strategies, including Value-Chain Analysis, Value-Chain Redesign and Change Mangement. Finally, Part IV (Implementing the 4th Dimension) explores the tools needed to implement the solutions developed in Parts I-III. It covers High-Velocity Management, a critical tool needed to put into action the high-level process transformations defined by the value-chain analysis detailed in Part III. It also details a strategic Change Management system that deals with on-going implementation and long-term maintenance issues.
What Is an E-Business? -- The New Playing Field -- Drivers of the E-World -- Taking the Plunge -- Business Drivers -- The Net Economy Meets the Global Economy -- People Drivers -- Process Drivers -- Technology Drivers -- Why the 4D Framework? -- An Introduction to the 4D Framework -- Into the Matrix -- The New Era -- The First Dimension: E-Drivers -- A New Definition for E-Organizations -- The Second Dimension: Phased Implementation -- Understanding Phase -- Solutions Phase -- Implementation Phase -- Maintenance and Monitoring Phase -- Change Continues -- The Third Dimension: Redesign Disciplines -- Value Chain Analysis -- Value Chain Linking -- High-Velocity Process Management -- Change Management -- Value Chain Analysis -- What Is a Value Chain? -- Basic Definition and Concepts of the Value Chain -- Value Chain Model Testing -- Putting It All Together -- Understanding Phase -- Solutions Phase -- Implementation Phase -- Maintenance and Monitoring Phase -- The Value Chain Linking Technique -- Value Chain Notation and Rules -- Value Chain Program and Value Chain Linking -- Value Chain Linking -- The Value Chain: A Detailed Link Map -- Where to Now? -- High-Velocity Process Management -- High-Velocity Process Management (HVPM) Revisited -- Understanding Phase -- Solutions Phase -- Implementation Phase -- Monitoring and Maintenance Phase -- Change Management -- Change Management in E-business -- The E-Change Management Process -- Value Chain Results-Based Change -- E-Change Management Models.
At head of title: Harris Kern's Enterprise Computing Institute.
includes index.
1
Keywords: CIT; Web sites; Electronic commerce